2020 8th International Conference on Cyber and IT Service Management (CITSM) 2020
DOI: 10.1109/citsm50537.2020.9268887
|View full text |Cite
|
Sign up to set email alerts
|

Using WebQual 4.0 For Measuring Quality of E-learning Services During COVID-19 Pandemic

Abstract: The purpose of this study is to measure the quality of website services in the form of STMIK Dipanegara Makassar e-learning in during the COVID-19 pandemic using WebQual 4.0, lecturers and students were asked to do the learning process from home, where STMIK Dipanegara Makassar provided e-learning that could be used by lecturers and students. This study recognizes differences in actual perceptions and ideal expectations of website users in the form of e-learning. The method used is WebQual 4.0, WebQual 4.0 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
0
9
0
7
Order By: Relevance
“…In a study of e-learning, the modern form of online learning, the following benefits were found [13], such as costeffectiveness, learning flexibility and, above all, the independent part.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study of e-learning, the modern form of online learning, the following benefits were found [13], such as costeffectiveness, learning flexibility and, above all, the independent part.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Model WebQual 4.0 telah melalui beberapa fase iterasi selama penyusunan instrumen evaluasi yang terbentuk menjadi tiga dimensi utama yaitu kegunaan, kualitas informasi, dan kualitas layanan interaksi [7][8][9][10] [11]. Berbagai penelitian telah mengadaptasi model WebQual untuk menilai kualitas website seperti pada domain website pemerintah [12][13] [14], website jasa layanan [15][16][17], dan website pendidikan [18][19] [20].…”
Section: Pendahuluanunclassified
“…Peneliti [19] menganalisa website yang dimiliki oleh Universitas Telkom untuk mengetahui kesenjangan antara harapan dengan persepsi pengguna, dan menetapkan atribut yang menjadi prioritas untuk dioptimalkan. Peneliti [20] menganalisa e-learning yang dimiliki oleh STMIK Dipanegara Makasar untuk mengetahui tingkat persentase penerimaan pengguna terhadap setiap dimensi atau variabel WebQual.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations